Values of the T-shaped Leader: Applying the 4M Framework to Address SoTL Grand Challenges and Foster Sustainable Development Goals in Higher Education - Hatfield, Lisa; Eady, Michelle; Abrahamson, Earle; Arcellana-Panlilio, Mayi; Namaste, Nina; Green, Corinne (Journal of University Teaching and Learning Practice, 2025)
This paper follows the conceptual T-shaped model, introduced by (the Authors), serving as a conduit for the dissemination of empirical data derived from engaging discussions with international Scholarship of Teaching and Learning (SoTL) scholars. The authors not only present the model, but also offer auto-ethnographic reflections, unravelling the key values embedded within it. These values, namely: context, contribution and co-creation, ethics of care, valuing, and research, are explored in-depth, highlighting their integral role in the T-shaped model. Expanding the foundational framework, this paper explores the interconnections between the T-shaped model's five values through the analytical lens of the 4M model, as articulated by Friberg (2016). This exploration spans all four levels: the personal (micro level), institutional (meso level), alignment with the recently released SoTL Grand Challenges (macro level) (Scharff et al., 2023), and a commitment to addressing the Sustainable Development Goals (SDGs) outlined by the United Nations (mega level). As higher education institutions (HEIs) worldwide ardently pursue the preparation of globally competent graduates, this paper highlights the imperative of well-informed institutions. These institutions, it argues, should not only champion the significance of teaching and learning but also conscientiously safeguard finite global resources. Acting as a guidepost for the journey ahead, this paper illuminates a path toward creating an educational landscape that aligns with contemporary challenges and strives to meet the evolving demands of the future. In doing so, it contributes to the ongoing discourse on advancing pedagogical practices for holistic higher education.